Clinical Efficacy of Prodom-Assisted Urokinase in the Treatment of Male Infertility Caused by Impaired Semen Liquefaction. (20th January 2021) - Mao, Kaiyi; Chen, Zongping; Li, Mengzhi; Gou, Chengren; Zhou, Zidong; Yan, Yong; Chen, Chao; Liu, Tong; Zou, Chenghong; Yao, Yuhong; Li, Xu
Abstract : Purpose . To evaluate the clinical efficacy of prodom in the administration of urokinase in the vagina in couples with impaired semen liquefaction. Materials and Methods . Overall, 261 patients with impaired semen liquefaction were randomly divided into prodom-assisted urokinase treatment (PAUT) group (n = 91 ), syringe-assisted urokinase treatment (SAUT) group (n = 86 ), and traditional treatment (TT) group (n = 84 ) in the first stage. If the first stage of treatment failed, other treatment methods were initiated instead and the patients were grouped according to the newer treatment method in the second stage. The pregnancy rate, time-to-conception, and treatment costs were evaluated in each group. Results . In the first stage, the pregnancy rate in the PAUT, SAUT, and TT groups was 69.23%, 29.07%, and 22.62%, respectively; the time-to-conception was 2.66 ± 1.44, 3.69 ± 2.61, and 3.86 ± 3.00 months, respectively; the treatment costs were 658.18 ± 398.40, 666.67 ± 507.50, and 680.56 ± 480.94 $, respectively. The pregnancy rate and time-to-conception were different in the PAUT group compared with those in SAUT and TT groups (all P < 0.05 ). However, the difference in treatment costs was not significant (P = 0.717 ). In the second stage, 154 nonpregnant patients were divided into nine treatment groups, and the effects of changing TT to PAUT on the pregnancy rate, time-to-conception, and treatment costs were observed to be different from those of other treatments (all P < 0.05 ). Conclusion . Prodom-assisted urokinase can effectively treat male infertility secondary to impaired semen liquefaction.